2020
DOI: 10.1111/iere.12497
|View full text |Cite
|
Sign up to set email alerts
|

Cognition, Optimism, and the Formation of Age‐dependent Survival Beliefs

Abstract: This paper investigates the roles psychological biases play in deviations between subjective survival beliefs (SSBs) and objective survival probabilities (OSPs). We model deviations between SSBs and OSPs through age-dependent inverse S-shaped probability weighting functions. Our estimates suggest that implied measures for cognitive weakness increase and relative optimism decrease with age. We document that direct measures of cognitive weakness and optimism share these trends. Our regression analyses confirm th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 85 publications
(132 reference statements)
0
3
0
Order By: Relevance
“…The predicted values for this exercise for target ages j ∈ {75, 85} are shown in Figure 5 for the nonblack population: individuals in bad health generally display a more negative bias than individuals in better health. 12 In a related paper, Grevenbrock et al (2021) estimate survival based on several additional characteristics besides self-reported health, age, and sex, such as smoking and drinking behavior, and chronic diseases. Grouping individuals based on their estimated objective survival probability, they find that individuals with low objective survival probability in general overestimate, while individuals with high objective probability underestimate their survival probabilities; in other words, at a first glance the reverse pattern compared to what we find.…”
Section: Expectation Errors In Survival Probabilitiesmentioning
confidence: 99%
See 1 more Smart Citation
“…The predicted values for this exercise for target ages j ∈ {75, 85} are shown in Figure 5 for the nonblack population: individuals in bad health generally display a more negative bias than individuals in better health. 12 In a related paper, Grevenbrock et al (2021) estimate survival based on several additional characteristics besides self-reported health, age, and sex, such as smoking and drinking behavior, and chronic diseases. Grouping individuals based on their estimated objective survival probability, they find that individuals with low objective survival probability in general overestimate, while individuals with high objective probability underestimate their survival probabilities; in other words, at a first glance the reverse pattern compared to what we find.…”
Section: Expectation Errors In Survival Probabilitiesmentioning
confidence: 99%
“…Many studies have documented the existence of an age bias in subjective life expectancies, and a few of the papers within this group are concerned with the implications for the consumption/savings behavior. Some predict individual survival probabilities and contrast them with elicited beliefs (Gan, Hurd, and McFadden (2005), Bissonnette, Hurd, and Michaud (2017), Grevenbrock, Groneck, Ludwig, and Zimper (2021)), but none of these look at the implications for within‐cohort savings behavior in a structural model where beliefs change in the event of health shocks, or analyze the implications for wealth inequality.…”
Section: Introductionmentioning
confidence: 99%
“…Mortality risk models were estimated using data on individuals' survival over the period 1995-2018 and data on SSPs for their survival beliefs. These models control for individual characteristics such as gender, socioeconomic status, and health behavior, which can be correlated with PLE-knowledge and related to survival or survival belief (e.g., Cutler, Deaton, andLleras-Muney 2006, 2011;Delavande and Rohwedder 2011;Grevenbrock et al 2020;Hurd and McGarry 2002;Kalwij, Alessie, and Knoef 2013;. The associations between the covariates and annual mortality belief (see Table 1, right columns) are in line with previous findings, especially in terms of health characteristics, such as having bad health, chronic illnesses, smoking and drinking alcohol (e.g., Teppa 2012;Bissonnette, Hurd, and Michaud 2017).…”
Section: Empirical Analysismentioning
confidence: 99%
“…One strand of the literature has studied the underlying reasons for biases in survival beliefs empirically. For example, Grevenbrock et al (2020) found that cognitive weakness, according to which people cannot distinguish well among respective likelihoods of events, increases with age and explains the underestimation (overestimation) of survival beliefs at age 65 (85). Similarly, Bago D'Uva, O 'Donnell, and van Doorslaer (2020) found that both men and women underestimate their subjective probability of living to age 75 compared to survival to that age, and that predictions errors are larger for the low-educated and those with low cognitive skills.…”
Section: Introductionmentioning
confidence: 99%
“…First of all, we verify if subjective beliefs imply under-estimation of survival at younger ages and over-overestimation at older ages. Previous studies already report evidence on this; see Hamermesh (1985), Perozek (2008), Zimper (2012), andGrevenbrock et al (2021). However, we differentiate from these papers by how we compute the objective counterpart of subjective probabilities, as we derive health-dependent actuarial probabilities accounting for diagnosed diseases instead of only classifying individuals according to age and gender using standard life tables.…”
Section: Empirical Analysismentioning
confidence: 99%